2012
DOI: 10.1007/s10103-012-1141-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of endovenous laser treatment of the incompetent great saphenous vein with external air cooling

Abstract: Endovenous laser treatment (ELT) has been proposed as an alternative in the treatment of reflux of the great saphenous vein. Before the procedure, peri-saphenous subcutaneous tumescent saline solution infiltration is usually performed. However, diffusion of this tumescent fluid is rapidly observed and can potentially reduce the efficacy as a heat sink. External skin cooling with cold air was proposed as an alternative solution. The objective of this study is to compare endovenous laser treatment without and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Even if the vein was located 5 mm below the skin, the surface temperature remained below 40°C. 12 This value is similar to the temperature measured at the surface of the skin with the infrared thermometer: 40.3 AE 1.8°C.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Even if the vein was located 5 mm below the skin, the surface temperature remained below 40°C. 12 This value is similar to the temperature measured at the surface of the skin with the infrared thermometer: 40.3 AE 1.8°C.…”
Section: Discussionmentioning
confidence: 90%
“…These results confirmed the numerical simulations that our group performed. 12 No skin burns were reported, and surgical time was significantly shorter than for ELT with tumescent anesthesia. Safety standards were upheld, and surgical and recovery times were drastically reduced.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…so called "hemoglobin-absorbing" and "water-absorbing" lasers) is generally unimportant for final thermal and consequently clinical effect. Numerical simulation of EVLA treatment of great saphenous vein (GSV) suggested that as long as the vein is located more than 10 mm below the skin surface the temperature of the skin does not exceed 45°C (6). Back in 2002 we noted that our patients who had undergone EVLA in intravenous sedation or regional anaesthesia due to either personal preferences or insurance requirements and treated without tumes-cent solution experienced actually less pain and bruising than those injected with the solution.…”
Section: Zusammenfassungmentioning
confidence: 90%